Time preferences and lifetime outcomes - Bart H. H. Golsteyn; Hans Grönqvist; Lena Lindahl (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2013)
This paper investigates the relationship between time preferences and lifetime social and economic behavior. We use a Swedish longitudinal dataset that links information from a large survey on children's time preferences at age 13 to administrative registers spanning over four decades. Our results indicate a substantial adverse relationship between high discount rates and school performance, health, labor supply, and lifetime income. Males and high ability children gain significantly more from being future-oriented. These discrepancies are largest regarding outcomes later in life. We also show that the relationship between time preferences and long-run outcomes operates through early human capital investments.
Keywords: D03; D91; J01; 330; intertemporal choice; personality; preference parameter; human capital; income; health